Association of Serum Zinc and Selenium Levels with Infection in Patients With Stroke - Mohammad Mahdi Majzoobi; Ali Akbar Javadi; Mehrdad Hajilooi; Amin Doosti-Irani; Mahyar Motaghed (Epidemiology and Health System Journal, 2024)
Background and aims: Patients with acute stroke are vulnerable to infectious diseases due to low consciousness, aspiration, dysphagia, and underlying conditions. Zinc and selenium play critical roles in boosting the immune system. This study aimed to compare serum zinc and selenium levels in patients with stroke before and after infection. Methods: The present prospective study was conducted on patients with stroke in Hamadan, west of Iran, from 2019 to 2020. Serum levels of zinc and selenium were measured before and after infection in patients with stroke. The calculated sample size for this study was 78 patients. A paired t-test was used to compare the mean zinc and selenium levels. The linear regression model was used to assess the association of clinical and para-clinical factors with the change in the serum level of selenium after infection. The level of statistical significance was 0.05. Results: The mean (±SD) age of participants was 71.33±14.27 years, and 55.1% of the participants were female. The mean (±SD) serum zinc levels before and after infection were 80.4±7.6 µg/dL and 74.3±7.9 µg/dL, respectively, indicating a significant difference (P<0.001). These values for selenium were 118.1±42.8 µg/dL and 78.4±29.4 µg/dL, respectively (P<0.001). There was a significant association between sepsis and decreases in the levels of selenium (-28.86 µg/dL, 95% CI: -56.13, -1.59) and zinc (-9.84 µg/dL, 95% CI: -16.12, -3.56). Conclusion: Based on our results, the levels of zinc and selenium in patients with stroke significantly decrease after infection compared to before infection.